THE INFLUENCE OF COMPENSATION AND WORK DISCIPLINE ON THE PERFORMANCE OF TEACHERS (TEACHERS) OF TAMAN SISWA PRIVATE VOCATIONAL SCHOOL AT THE TAMAN SISWA PRIVATE VOCATIONAL SCHOOL FOUNDATION - Jopinus Saragih (International Journal of Teaching and Learning, 2024)
This research aims to find out how compensation and work discipline influence the performance of teachers (teachers).The population in this study were all civil servants (teachers) at Taman Siswa Tebing Tinggi School totaling 51 people, consisting of 19 people from SMK Business Management and 32 people from SMK TSM. The sample taken was 51 respondents using census techniques, namely the entire population was sampled. The regression analysis method used is multiple linear regression and to test the hypothesis the t test and f test are used at the significance level or alpha = 5%. The research data were analyzed or processed using the SPSS version 17 program. Based on the research results thatof 0.696 or 69.6%. This shows that the compensation variable (X1) and work discipline variable (X2) can explain the performance variable (Y) by 69.6%, the remaining 30.4% (100% - 69.6%) is explained by other variables outside this research model.In the results of the multiple linear regression test, the following regression equation is obtained:Y = 3.975 + 0.620X1 + 0.245X2 + e. The results of the hypothesis test state that: H1 is accepted, this can be seen from the tcount value of 4.479 > ttable 2.009 and with a significance value of 0.000 < 0.05, compensation has an effect on the performance of the tutor (teacher). H2 is accepted, this can be seen from the tcount value which is 2.375 > ttable 2.009 and with a significance value of 0.022 <0.05 then work discipline influence the performance of tutors (teachers). H3 is accepted, this can be seen from the Fcount value which is 58.346 > Ftable 3.19 with a significance value of 0.000 <0.05, so compensation and work discipline have a joint (simultaneous) effect on performance.